Dopuszczalność żądania wydania przez doradcę podatkowego dokumentacji księgowej podatnika organom kontroli skarbowej w toku postępowania kontrolnego poza procedurą kontroli podatkowej - Nykiel, Włodzimierz; Wilk, Michał (Kwartalnik Prawa Podatkowego, 2015)
Requesting submitting of tax documentation from tax advisor, formulated by a tax audit authority in the course of the audit proceedings outside the procedure of tax audit is inadmissible on the grounds of the regulations of tax law. Such in instrument is reserved exclusively for tax authorities in the course of tax audit procedure. That being so there are no legal grounds for criminal charges for tax advisor who refuses to submit tax documentation of a taxpayer outside the tax audit procedure.